Economic theory and the ancient Mediterranean - Jones, Donald W. (Chichester, West Sussex : Wiley-Blackwell, 2014)
Economic Theory and the Ancient Mediterranean presents a comprehensive introduction to the application of contemporary economic theory to the ancient societies of the Mediterranean Sea from the period of 5000 BCE to 400 CE. Offers an accessible presentation of modern economic theory and its relationships to ancient societiesPresents innovative expositions and applications of economic theory to issues in antiquity not often found in the literatureFeatures insightful discussions of the relevance of contemporary economic models to various situations in antiq... .
4.8 The Economics of Mycenaean Vases, III: Industry Structure4.9 Ancient Monopoly and Oligopoly: Religion and Foreign Trade; References; Suggested Readings; Notes; Chapter 5 General Equilibrium; 5.1 General Equilibrium as a Fact and as a Model; 5.1.1 The facts; 5.1.2 The models; 5.1.3 The questions; 5.2 The Walrasian Model; 5.3 Exchange; 5.4 The Two-Sector Model; 5.4.1 The basics with the Lerner-Pearce diagram; 5.4.2 Growth in factor supplies; 5.4.3 Technical change; 5.5 Existence and Uniqueness of Equilibrium; 5.6 Computable General Equilibrium Models; References; Suggested Readings; Notes.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Econometrics; Mediterranean Region -- History -- To 476.; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; Econometrics; Mediterranean Region -- Economic conditions; Mediterranean Region -- History -- To 476.; Mediterranean Region -- Economic conditions; Electronic books; Electronic books; Electronic books